1996
DOI: 10.1097/00000542-199606000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Normothemic Continuous Blood Cardioplegia Improves Electrophysiologic Recovery after Open Heart Surgery

Abstract: The current prospective human study suggests that the increased susceptibility for ventricular fibrillation and dysrhythmia, and the delayed recovery of the conduction system after hypothermic myocardial protection, are related to temperature-induced changes in vital cellular functions of the conduction tissue in the postischemic period. Both cardioplegic methods provide adequate myocardial protection but normothermic oxygenated blood cardioplegia may accelerate recovery of the heart after cardiopulmonary bypa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…At present, the incidence of new persistent CDs at our hospital is somewhat less than 1%, although the same type of crystalloid cardioplegia is used. It has been suggested that delayed recovery of the conduction system after hypothermic myocardial protection is related to temperature-induced ehanges in vital cellular functions of the conduction tissue during the postischaemic period (18). In attempting to discern other factors that would predispose the patients to develop conduction disturbances, we examined several variables, of which four remained significant after further analysis: preoperative left main coronary artery stenosis, intraoperative myocardial infarct with early postoperative enzyme release, and prolonged administration in the cardiac care unit.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the incidence of new persistent CDs at our hospital is somewhat less than 1%, although the same type of crystalloid cardioplegia is used. It has been suggested that delayed recovery of the conduction system after hypothermic myocardial protection is related to temperature-induced ehanges in vital cellular functions of the conduction tissue during the postischaemic period (18). In attempting to discern other factors that would predispose the patients to develop conduction disturbances, we examined several variables, of which four remained significant after further analysis: preoperative left main coronary artery stenosis, intraoperative myocardial infarct with early postoperative enzyme release, and prolonged administration in the cardiac care unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, following successful reports of normothermic CPB [5] there was an increased use of warm heart surgery techniques. Normothermic bypass has been shown to have various systemic advantages including increased cardiac output [6], improved myocardial function [7], reduced bleeding complications [8], shorter time to extubation and length of hospital stay. However, along with these advantages, there have been reports of increased incidence of adverse neurological events in warm bypass groups [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Various benefits have been reported, including increased cardiac output [6], improved myocardial function [7], reduction in respiratory demand, reduced bleeding and reduced time to extubation [8]. However, with these benefits came concerns of increased incidence of neurological deficits [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…At least 17 trials that compared warm or tepid blood cardioplegia with cold blood or crystalloid cardioplegia have been published in peer-reviewed, English-language journals. 1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Most of the studies enrolled Ͻ100 patients, whereas the Emory trial 11 (which was stopped prematurely because of an excess of neurological events in the warm cardioplegia group) and the Toronto study 1 each involved Ͼ1000 patients. Although the majority of the studies favored warm cardioplegia, smaller studies were generally powered only to detect differences in sensitive surrogate end points.…”
Section: Iii-341mentioning
confidence: 99%